History in Motion: Colonial Williamsburg - Nikola Krstović (EXARC, 2018)
Boundaries are always an interesting topic. In the framework of the current heritage buzz word decolonization, boundaries might also represent what is “colonised” in every cultural enterprise, or to be more specific, how and why some form of power obtruded its authority, and to what extent. Like almost all other museums, Colonial Williamsburg deals with the past. The past has its own boundaries that make the framework even more specific, to the period of early American history. Yet, CW’s mission is clear about being a dot in timeline – a bridge between a “chosen” past and future yet to be created. The paper is a result of a month-long research project granted through the fellowship of John D. Rockefeller, Jr. Library of the Colonial Williamsburg Foundation and EXARC.